2012
DOI: 10.1590/s1679-87592012000200002
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of contamination by oil and oil products in the Santos-São Vicente estuary, São Paulo, Brazil

Abstract: A B S T R A C TDifferent components of the mixed function oxidase (MFO) system and the levels of fluorescent aromatic compounds in bile (FACs) were measured in Cathorops spixii in order to assess the impact of polycyclic aromatic hydrocarbons (PAHs). Fish were sampled in an estuary (Santos/São Vicente) with a history of contamination by PAHs, mainly due to the presence of the industrial complex of Cubatão city and of another of low anthropogenic influence (Cananéia) on the Brazilian coast. FACs were higher in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Previous studies reported high concentration of different types of pollutants in water of the region of Santos-São Vicente Estuary (Azevedo et al, 2009(Azevedo et al, , 2012Carmo, Abessa, & Machado-Neto, 2012;Albergaria-Barbosa et al, 2017Magalhães, Taniguchi, Lourenço, & Montone, 2017;Souza et al, 2018). In this area, the presence of phosphorus, nitrogen, organic carbon, metals (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies reported high concentration of different types of pollutants in water of the region of Santos-São Vicente Estuary (Azevedo et al, 2009(Azevedo et al, , 2012Carmo, Abessa, & Machado-Neto, 2012;Albergaria-Barbosa et al, 2017Magalhães, Taniguchi, Lourenço, & Montone, 2017;Souza et al, 2018). In this area, the presence of phosphorus, nitrogen, organic carbon, metals (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…others organic contaminants ( Pérez et al., 2014 ; Sanchís et al, 2013 , 2015 ) have identified the presence of these compounds at levels even higher than that established by the European legislation, which ranges between 1.0 and 10 μg kg −1 , depending on the type of food ( EFSA, 2008 ). The level of contamination and/or the process within the raw material processing can influence the increase, reaching the by-products ( Bettin and Franco 2005 ; Tfouni, 2007 ; Camargo et al., 2011 ; Azevedo et al., 2012 ). Even at minimum percentages of PAHs, their toxicity is high, since some PAHs are considered potentially carcinogenic and genotoxic ( IARC, 2014 ; WHO, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The level of contamination and/or the process within the raw material processing can influence the increase, reaching the by-products (Bettin and Franco 2005;Tfouni, 2007;Camargo et al, 2011;Azevedo et al, 2012). Even at minimum percentages of PAHs, their toxicity is high, since some PAHs are considered potentially carcinogenic and genotoxic (IARC, 2014;WHO, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…have been detected in SB due to contamination sources Patire et al (Martins et al, 2007;Kim et al, 2016;Magalhães et al, 2017;Fontes et al, 2019). Petroleum exploration also contribute to the release of PAHs in the region (Azevedo et al, 2012), especially in SCS. This activity has increased substantially in the last decade, making it necessary to establish a monitoring program in the area.…”
mentioning
confidence: 99%